Analisa Pengukuran Kualitas Layanan Website Fakultas Teknik Universitas Janabadra Menggunakan Metode Webqual - Setyorini, Agustin (Universitas Janabadra, 2016)
To determine the quality of services provided and to determine what factors influence the quality of website services Janabadra University Faculty Tekink used methods WebQual 4.0 to satisfaction of users that can be used as consideration in fixing the flaws in the service website Janabadra Faculty of Engineering University of Yogyakarta. WebQual is one method or technique of measuring kualirtas website based on the perception of end users. There are 3 dimensions in WebQual 4.0 ie Dimensions Ease of Use, Quality of Information and Dimensions Dimensions Interaksi.Penelitian Quality is done by looking to study literature, and use the questionnaire to collect the data needed. Based on the analysis states that the overall dimensions of the ease of users is an aspect which is more prominent than the other two dimensions. Key words: Website, WebQual, Kepuasan Pengguna